Frailty and quality of life in elderly patients with acute coronary syndrome - Lisiak, Magdalena (Clin Interv Aging, 2016)
BACKGROUND: Frail elderly people are at risk of developing adverse health outcomes such as disability, hospitalization, and mortality. In recent years, the literature has drawn attention to the role of frailty syndrome (FS) in acute coronary syndrome (ACS). There are few studies regarding the relationship between two multidimensional variables such as FS and quality of life (QoL). OBJECTIVE: The aim of the study was to investigate the relationship between FS and early QoL of elderly patients with ACS (≥65 years old). METHODS: The study was conducted among 91 patients aged 65 years and over with ACS. The MacNew questionnaire was used to evaluate QoL and the Tilburg frailty indicator to evaluate frailty. RESULTS: FS was present in 82.4% of patients. The average Tilburg frailty indicator score was 7.43±2.57. A negative correlation between the global values of FS and QoL was shown (r=−0.549, P<0.05). The vulnerability factors that negatively affected early QoL were: FS, marital status, conservative therapy, and hypertension. In multivariate analysis, FS was found to be the independent predictor of worse QoL (β ± standard error −0.277±0.122, P=0.026). CONCLUSION: The presence of FS has a negative impact on early QoL in patients with ACS. The study suggests that in elderly patients with ACS, there is a need to identify frailty in order to implement additional therapeutic and nursing strategies in ACS.